Remote Lab Generator (RLGen): A software tool using auto-generating technique to develop a remote lab - Hasnim, H.; Abdullah, M. Z. (International Journal of Online and Biomedical Engineering (iJOE), 2007)
Recent Remote Lab development shows that there are many implementation models and architectures which can be used to develop a remote lab. A technique which aims at generating and automating processes and tasks can simplify this development. A new software prototype named Remote Lab Generator (RLGen) uses this technique to demonstrate how the development process of a remote lab can be made easier for lab instructors.